Let $f: A \rightarrow B$ and $g: B \rightarrow C$ be the bijective functions. Then, $(g o f)^{-1}=$

(a) $f^{-1} \circ g^{-1}$

(b) fog

(c) $g^{-1} o r^{-1}$

(d) gof


Given: f : A → B and g : B → C be the bijective functions

Since, $f: A \rightarrow B$

Thus, $f^{-1}: B \rightarrow A$                $\ldots(1)$

Since, $g: B \rightarrow C$

Thus, $g^{-1}: C \rightarrow B$              $\ldots(2)$

From (1) and (2), we get

$f^{-1} \mathrm{og}^{-1}: C \rightarrow A$       $\ldots(3)$

Also, $g o f: A \rightarrow C$

$\Rightarrow(g o f)^{-1}: C \rightarrow A$               $\ldots(4)$

Therefore, $(g o f)^{-1}=f^{-1} \mathrm{og}^{-1}$

​Hence, the correct option is (a).

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now